2010
DOI: 10.1248/bpb.33.1716
|View full text |Cite
|
Sign up to set email alerts
|

Isofraxidin, a Coumarin Component from Acanthopanax senticosus, Inhibits Matrix Metalloproteinase-7 Expression and Cell Invasion of Human Hepatoma Cells

Abstract: Invasion and metastasis of cancer cells are the major causes of high motality in cancer patients. Matrix metalloproteinases (MMPs) are zinc-dependent proteolytic enzymes capable of degrading the components of extracellular matrix (ECM), including type IV collagen, gelatin and fibronectin. Cancer cells destruct surrounding tissues by enzymatic action of MMPs, leading to cancer invasion and metastasis. Among several MMPs, MMP-2, -7 and -9 are considered to be involved in cancer invasion and metastasis. In partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 22 publications
0
40
0
Order By: Relevance
“…GA and proanthocyanidins have been shown to arrest the cell cycle, induce apoptosis, inhibit angiogenesis and tumor invasion in vitro (Ji et al, 2009;Ho et al, 2010;Madlener et al, 2007;Nandakumar et al, 2008). Anti-proliferative activity has also been reported for simple coumarins like 7-hydroxycoumarin (LopezGonzalez et al, 2004;Elinos-Báez et al, 2005), esculetin (Chu et al, 2001;Lee et al, 2008), 4-hydroxycoumarin (Velasco-Velázquez et al, 2003isofraxidin (Borris et al, 1980;Yamazaki and Tokiwa, 2010) and 7,8-dihydroxy-4-methyl coumarin (Riveiro et al, 2008). These coumarins were observed to arrest the cell cycle, induce apoptosis and inhibit tumor cell migration and invasion.…”
Section: Dpph Abtsmentioning
confidence: 99%
“…GA and proanthocyanidins have been shown to arrest the cell cycle, induce apoptosis, inhibit angiogenesis and tumor invasion in vitro (Ji et al, 2009;Ho et al, 2010;Madlener et al, 2007;Nandakumar et al, 2008). Anti-proliferative activity has also been reported for simple coumarins like 7-hydroxycoumarin (LopezGonzalez et al, 2004;Elinos-Báez et al, 2005), esculetin (Chu et al, 2001;Lee et al, 2008), 4-hydroxycoumarin (Velasco-Velázquez et al, 2003isofraxidin (Borris et al, 1980;Yamazaki and Tokiwa, 2010) and 7,8-dihydroxy-4-methyl coumarin (Riveiro et al, 2008). These coumarins were observed to arrest the cell cycle, induce apoptosis and inhibit tumor cell migration and invasion.…”
Section: Dpph Abtsmentioning
confidence: 99%
“…In addition, it acts at the transcription level to regulate inflammatory modulators, such as IκBα and NF-κB, that could affect downstream genes involved in the inflammatory response, including iNOS, COX-2, and TNF-α [22]. However, many studies have shown that IF did not suppress COX-2 gene expression pronounced [20,25,26]. It was also reported that IF showed an inhibitory effect on the phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2) in hepatoma cells, but it showed little effect on activator protein-1 (AP-1) DNA binding activity, nuclear factor-kappa B (NF-κB) nuclear translocation, and inhibitory kappa B (IκB) degradation [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have shown that IF did not suppress COX-2 gene expression pronounced [20,25,26]. It was also reported that IF showed an inhibitory effect on the phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2) in hepatoma cells, but it showed little effect on activator protein-1 (AP-1) DNA binding activity, nuclear factor-kappa B (NF-κB) nuclear translocation, and inhibitory kappa B (IκB) degradation [26]. All these findings strongly suggest that IF may have a significant effect on inflammation and play an important role in the MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…proliferation and transformation, and is associated with the invasion and metastasis of cancer cells. Therefore, the ERK MAPK signaling pathway is one of the most important targets for the development of anti-cancer drugs (Yamazaki and Tokiwa, 2010;Johnson et al, 2010). Recent studies have demonstrated that ERK1/2 and p38 regulate trophoblasts differentiation in human term placenta (Daoud et al, 2005), and the ERK signaling pathway may be essential for regulating the balance between proliferation and apoptosis in CD34 + -derived neutrophil progenitor cells (Geest et al, 2009).…”
Section: Discussionmentioning
confidence: 99%